Associations between smoking and osteoporosis and all-cause mortality in participants from the United States: a cohort study - Qu, Xiaoqin; Jiang, Jingcheng; Deng, Qingshan; Wang, Han; Zhang, Chao; Xu, Xiaoping; Yi, Yong; Qiu, Lihua (Frontiers in Endocrinology, 2025)
BackgroundSmoking is a global public health concern, with approximately 1,245 billion smokers worldwide. It is associated with a range of health complications, including cardiovascular and respiratory diseases. Osteoporosis, characterized by reduced bone density and deterioration of bone tissue, has a global prevalence of 18.3%, with higher rates in women over the age of 50. Smoking has been recently associated with osteoporosis, potentially due to shared metabolic disorders or personal habits. This study aimed to investigate the association between smoking and osteoporosis in relation to all-cause mortality in a cohort from the United States.MethodsData were sourced from the National Health and Nutrition Examination Survey (NHANES) database, which focuses on individuals aged 20 years and older from 2005–2010, 2013–2014, and 2017–2018, where femoral neck bone density testing was conducted. The participants were categorized on the basis of their self-reported smoking status and bone mineral density (BMD) measurements, following the World Health Organization criteria for osteoporosis. The covariates included age, sex, race, alcohol consumption, BMI, blood glucose levels, and other health indicators. Statistical analysis included ANOVA and chi-square tests for baseline characteristics, Kaplan–Meier survival analysis, and multivariate Cox regression analysis to assess hazard ratios (HRs) and 95% confidence intervals (CIs) for all-cause mortality. We divided the patients into four different groups via a cross-classification method on the basis of smoking status and whether they had osteoporosis.ResultsThis study included 19,400 participants, with significant differences in baseline characteristics across 4 groups (S-/OP+: nonsmokers with osteoporosis; S+/OP-: smokers without osteoporosis; S-/OP-: nonsmokers without osteoporosis; S+/OP+: smokers with osteoporosis). The overall average age was 53.1 years, and women accounted for 49.6% of the total population. The mortality rate due to all factors in the total population was 13.1%, with the highest S+/OP+ mortality rate. Participants with both a smoking history and osteoporosis had a 146% increase in all-cause mortality (HR: 2.46, 95% CI: 2.12–2.87) even after adjusting for confounding factors. The relative excess risk due to interaction (RERI) suggested a lack of statistical significance, whereas the attributable proportion (AP) indicated a synergistic effect between smoking and osteoporosis.ConclusionsThis cohort study highlights the importance of managing and preventing smoking and osteoporosis to reduce the risk of all-cause mortality. The findings provide preliminary evidence of a synergistic effect between smoking and osteoporosis on all-cause mortality risk, emphasizing the need for proactive strategies for smoking cessation and close monitoring of risk factors in individuals with both conditions.